Dataset DrivAer hp-F: Surface Pressure Measurements in Yaw Conditions - Rijns, Steven; Teschner, Tom-Robin; Blackburn, Kim; Ramos Proenca, Anderson; Brighton, James (Cranfield University, 2024)
Dataset for the surface pressure measurements conducted on the 35% scale DrivAer hp-F model at various yaw angles in the 8x6 Wind Tunnel at Cranfield University. The dataset includes the surface pressure coefficient results from measurements on the slant of the following vehicle configurations: - DrivAer hp-F standard configuration (no spoiler or rear wing) - DrivAer hp-F spoiler configuration - DrivAer hp-F rear wing configuration The measurements on the DrivAer hp-F rear wing configuration have been conducted three times for repeatability. The dataset also includes a log file of the data structure and wind tunnel conditions for each experiment. In reference to the publication: Steven Rijns, Tom-Robin Teschner, Kim Blackburn, Anderson Ramos Proenca, James Brighton; Experimental and numerical investigation of the aerodynamic characteristics of high-performance vehicle configurations under yaw conditions. Physics of Fluids 1 April 2024; 36 (4): 045112. https://doi.org/10.1063/5.0196979 CAD files for the DrivAer hp-F configurations are available at: Rijns, Steven; Teschner, Tom-Robin; Blackburn, Kim; Ramos Proenca, Anderson; Brighton, James (2024). DrivAer hp-F: Spoiler & Rear Wing Configurations Geometry Pack. Cranfield Online Research Data (CORD). Dataset. https://doi.org/10.17862/cranfield.rd.25715202
Keywords: DrivAer'; 'Wind Tunnel'; 'Aerodynamics'; 'Automotive'